Simultaneous vertebral and subclavian artery stenting - Maciejewski, Damian; Tekieli, Łukasz; Machnik, Roman; Kabłak-Ziembicka, Anna; Przewłocki, Tadeusz; Paluszek, Piotr; Trystuła, Mariusz; Musiał, Robert; Dzierwa, Karolina; Pieniążek, Piotr (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2017)
Introduction: Vertebrobasilar territory ischemia leads to disabling neurological symptoms and may be caused both by vertebral artery (VA) and subclavian artery (SA) stenosis. The coexisting symptomatic ipsilateral VA and proximal SA stenosis should be considered as a true bifurcation lesion for percutaneous treatment. Aim : To evaluate the safety and efficacy of simultaneous angioplasty of vertebral and subclavian stenosis. Material and methods: Fifteen patients (age 69.5 years, 46.7% men, all symptomatic from posterior circulation (history of stroke, transient ischemic attack, chronic ischemia symptoms)) were scheduled for simultaneous SA/VA angioplasty. Clinical and duplex ultrasound follow-up was conducted 1, 6 and 12 months after the procedure. Results: The technical success rate was 100%. Single balloon-mounted stent angioplasty was performed for all VAs and for 13 (86.7%) SAs. In 4 cases a simultaneous radial and femoral approach was required. The mean North American Symptomatic Carotid Endarterectomy Trial (NASCET) VA stenosis was reduced from 88.7 ±9.7% to 5.7 ±6.8% and SA stenosis from 80 ±12.2% to 11 ±12.3% (p < 0.01). No periprocedural death, stroke, myocardial infarction or transient ischemic attack occurred. During follow-up (range: 6–107 months) in 10 of 15 (66.7%) patients relief of chronic ischemic symptoms was observed. No stroke/TIA occurred. One cardiovascular and 2 non-cardiovascular deaths were recorded. There was 1 symptomatic vertebral and 1 subclavian in-stent restenosis, and 2 cases of asymptomatic VA in-stent occlusion occurred. Conclusions : Simultaneous vertebral and subclavian artery stenting is safe and effective. The restenosis rate remains at an acceptable level and it may be treated successfully with drug-eluting balloon angioplasty. In selected patients a dual radial and femoral approach may facilitate the procedure.